SISTEM INFORMASI PORTAL BERITA MASJID BERBASIS WEB MENGGUNAKAN METODE EXTREME PROGRAMMING DI KOTA TANGERANG (Studi Kasus : DMI Kota Tangerang) - Nasrullah; Niki Ratama (Journal of Research and Publication Innovation, 2023)
The design of the mosque news portal application uses the extreme programming method which is used for data collection on mosques and activity news as well as an infaq/sodaqoh donation payment system. This mosque news portal application was made based on the problems encountered in the mosque data collection system in the city of Tangerang, where the mosque data collection system and mosque news were not optimal and there was a lack of transparency of information regarding mosque data collection and news on mosque activities in the city of Tangerang. The purpose of making this application is to make it easier for mosque administrators to collect data on mosques and provide the latest news information to the public through a website. This application is made using the PHP programming language with the CodeIgniter 3 framework, Javascript and MySQL database. The design was designed using HTML and CSS with the Bootstrap 5 framework. The expected result of making this application is that the data that was managed manually can be computerized and can be used by mosque administrators and mosque data collection and activity news quickly, precisely and accurately and can give confidence information.